TUBEROUS SCLEROSIS: A RARE CASE REPORT - Dr. Yaduraj; Dr. Prem Patel; Dr. Himanshu Adwani; Dr. Pranay Trivedi (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background:Tuberous sclerosis complex (TSC) is a rare autosomal dominant neurocutaneous disorder caused by mutations in either the TSC1 or TSC2 genes. It is characterized by hamartomas affecting multiple organ systems, most commonly the brain, skin, kidneys, heart, and lungs. Although seizures and neurodevelopmental delays are common, presentations can be variable, and dermatological signs may serve as early clues.Case Presentation:A 6-year-old male child presented with abdominal pain at a previous surgical site and notable facial skin lesions. On examination, characteristic dermatological findings included a hypopigmented ash leaf macule, facial angiofibromas (adenoma sebaceum), and a shagreen patch. Radiological investigations revealed bilateral renal angiomyolipomas, subependymal calcified nodules, and cortical tubers. Despite the absence of seizures, diagnostic criteria for TSC were fulfilled based on dermatological and neuroimaging findings.Conclusion:This case underscores the importance of thorough dermatological and imaging assessments in the early diagnosis of TSC, even in the absence of classic neurological symptoms. Multidisciplinary management is crucial to improving long-term outcomes.